2022
DOI: 10.1259/bjro.20210029
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to explore opinions of Saudi Arabian radiologists concerning AI-based applications and their impact on the future of the radiology

Abstract: Objective: The aim of this study was to explore opinions and views towards radiology AI among Saudi Arabian radiologists including both consultants and trainees. Methods: A qualitative approach was adopted, with radiologists working in radiology departments in the Western region of Saudi Arabia invited to participate in this interview-based study. Semi-structured interviews (n = 30) were conducted with consultant radiologists and trainees. A qualitative data analysis framework was used based on Miles and Huber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our responders were mostly from the private sector, men, from different medical areas and different ages, which was important to investigate the general perception of medical AI and if physicians more recently graduated were more prone to accept AI solutions than physicians longer graduated. Most of the studies in medical AI acceptance are focused in specific areas, such as radiology (5,6,7,8), dermatology(1, 9, 10, 11) and ophthalmology (12,13,14), which could be more affected than others by adoption of AI solutions. Thus, it is important to have more general views about the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Our responders were mostly from the private sector, men, from different medical areas and different ages, which was important to investigate the general perception of medical AI and if physicians more recently graduated were more prone to accept AI solutions than physicians longer graduated. Most of the studies in medical AI acceptance are focused in specific areas, such as radiology (5,6,7,8), dermatology(1, 9, 10, 11) and ophthalmology (12,13,14), which could be more affected than others by adoption of AI solutions. Thus, it is important to have more general views about the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a study conducted in the United States reported that none of the attending radiologists and only a very small proportion of the trainees believed that their jobs would be obsolete in the next 10–20 years [ 18 ]. In Saudi Arabia, radiology professionals believe that AI can potentially change the workflow in radiology with no effect on job security [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our responders were mostly from the private sector and male and belonged to different medical areas and age groups, which was important to investigate a broader perception of medical AI. Most of the studies in medical AI acceptance were focused on specific areas, such as radiology [5][6][7][8], dermatology [1,[9][10][11], and ophthalmology [12][13][14], which could be more affected than others by the adoption of AI solutions. Thus, it is important to have more general views about the topic.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Opinion surveys are important tools in assessing satisfaction with a particular service and consist of a list of questions whose objective is to extract certain data from a group of people [8]. Previous studies on the acceptance of the use of AI in medicine were limited to specific areas, such as radiology [5,[9][10][11], dermatology [1,[12][13][14], and ophthalmology [15][16][17], as well as to specific countries. However, at the time of writing, we were unable to find studies exploring this subject among Brazilian physicians, and there are very few studies in Latin America, leaving a gap in this part of the globe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation